In Situ Techniques for Probing Kinetics and Mechanism of Hollowing Nanostructures through Direct Chemical Transformations. Issue 11 (14th August 2018) - Wu, Siyu; Sun, Yugang
Abstract: Chemical transformation of nanostructures into hollow ones becomes important in the synthesis of materials with unique properties for applications ranging from sensing to energy storage, to high‐performance catalysis. The nanoscale Kirkendall effect and galvanic replacement represent two typical mechanisms responsible for hollowing nanostructures. These two mechanisms occur either independently or simultaneously to form hollow nanostructures with appropriate geometries and desirable properties. Precisely distinguishing the hollowing mechanism and kinetics involved in a chemical transformation relies on in situ characterization methods including in situ electron microscopy, in situ optical spectroscopy, and a suite of in situ synchrotron X‐ray techniques (e.g., imaging, scattering, and X‐ray absorption fine structure spectroscopy). Here, the two typical hollowing mechanisms and the in situ characterization extensively explored in recent years are summarized, providing a timely overview of the promise of in situ methods in studying nanoparticle evolution under real reaction conditions. Abstract : An overview of recent advances of in situ characterization of chemically transforming solid nanostructures to hollow ones is presented. In situ electron microscopy, in situ optical spectroscopy, and in situ synchrotron X‐ray techniques (including imaging and scattering) are comprehensively summarized and discussed as to how these in situ methods help understand the complicated hollowing mechanism and kinetics.